ABOUT THE TURKIC AND MONGOLIAN TRIBES IN THE MEDIEVAL MANUSCRIPT "TAVARIKH-I GUZIDA - NUSRAT-NAME - Zhumabaeva А.А.; Margulan А.С. (Journal of Oriental Studies, 2024)
The article provides a translation of part of the London manuscript «Tavarikh-i guzida - nusrat-name» No. 3222, which is kept in the British Museum (Great Britain) and has long been not unavailable to our oriental historians for translation. The goals and objectives of the research are the translation of the medieval manuscript, and the introduction of the new data on the origin of the Turkic and Mongolian tribes of the Golden Horde that joined the army of Genghis Khan or fought him into scholarly discourse. Initial methods of research include, first of all, the translation of the manuscript from the ancient Turkic into Russian, followed by a multifaceted comparative analysis and its correlation with historical data. The results of the research are unique data on the indigenous Mongolian tribes of Nirun Mongols and the Darlekins, a group of Turkic tribes that allied themselves with the Mongols. Both groups are part of the Khamag-Mongol conglomerate, which founded the All-Mongolian state and subsequently became the core of the Mongolian nation. Besides, after the collapse of the Golden Horde, some of the tribes of the Turkic Darlekin Mongols became part of the Kazakh Khanate and assimilated with the Kazakhs. Conclusions. In the course of studying the composition of the Turkic and Mongolian tribes, it becomes possible to obtain new data on the history of building of the Mongolian and Kazakh ethnic groups on the basis of historical sources as well as through the lens of historical events. Keywords. The Great Mongolian state, Jochi Ulus, Alan-Goa, Genghis Khan’s army, Mongolian tribes, Turkic tribes, Oriental manuscripts, the Middle Ages.